2005
DOI: 10.1002/tox.20141
|View full text |Cite
|
Sign up to set email alerts
|

Interseasonal variability in biomarkers of exposure in fish inhabiting a southwestern Australian estuary

Abstract: The Swan-Canning Estuary, in southwestern Australia, undergoes distinct seasonal changes, with freshwater discharge predominant in the winter (wet) season and low flow with high salinity predominant in the dry summer season. To investigate seasonal variability in biomarkers of exposure in fish, black bream (Acanthopagrus butcheri) were collected from seven sites in the Swan-Canning Estuary in winter 2000 and in summer 2001. No interseasonal or intersite differences in serum sorbitol dehydrogenase concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…2A). Webb and Gagnon (2002) and Webb et al (2005), found a similar pattern in the Swan-Canning river, Western Australia, in which males at all sites, had a higher EROD activity than female fish. In the present study, male croaker had significantly higher EROD activity level than the females, most likely due to reproductive activity, supporting the finding by Hodson et al (1991) that the reproductive status can significantly affect EROD activity in fish.…”
Section: Discussionsupporting
confidence: 65%
“…2A). Webb and Gagnon (2002) and Webb et al (2005), found a similar pattern in the Swan-Canning river, Western Australia, in which males at all sites, had a higher EROD activity than female fish. In the present study, male croaker had significantly higher EROD activity level than the females, most likely due to reproductive activity, supporting the finding by Hodson et al (1991) that the reproductive status can significantly affect EROD activity in fish.…”
Section: Discussionsupporting
confidence: 65%
“…This method is also useful to examine the ratio between types of PAHs. The ratio of PAH metabolites can be used to indicate the origin of PAH contamination (6,19,25,26). The FF analysis of bile measures groups of PAH metabolites, with the naphthalene-type comprised mainly of two-ring structures, the phenanthrene-type mainly three-ring structures, pyrene-type mainly four-ring structures, and the B(a)P-type mainly five-ring structures (4).…”
Section: Discussionmentioning
confidence: 99%
“…As many fish species are highly mobile, measurement of biomarkers is often a more reliable method for assessing exposure to PAHs than measuring PAHs in the sediment where the fish were captured, and bioavailability is taken into account (5). Also, fish can metabolize PAHs to form reactive metabolites, which subsequently can bond covalently as adducts to cellular macromolecules, such as DNA, RNA, and proteins (6).…”
Section: Introductionmentioning
confidence: 99%
“…Aus: Baker et al, 2016;Duarte et al, 2017;Fu et al, 2017b;Gagliano et al, 2011;Gagnon and Rawson, 2016;Goodall et al, 2016;Hassell et al, 2016;Humphrey et al, 2007;Mai and Fotedar, 2017;Shaw et al, 2004;Webb and Gagnon, 2013;Webb et al, 2005NZ: Chandurvelan et al, 2015 Biotransformation Phase I (Cytochrome P450) Transformation of hydrophobic chemicals via oxidation, reduction and hydrolysis to more polar products.…”
Section: All Pollutantsmentioning
confidence: 99%